Bridging the Traditional and the Digital: Practices of Indonesia’s Tarekat Qadiriyya and Naqsyabandiyya - Siswoyo, Siswoyo Aris Munandar; Fahrurrozi, Fahrurrozi (Journal of Asian Wisdom and Islamic Behavior, 2023)
Sufism is often regarded as a doctrine that demands individuals to abandon worldly life and live in simplicity. However, Tarekat Qadiriyya and Naqsyabandiyya differs because it plays an important role in developing social, economic, and digital aspects of Indonesian society. This Sufi order has made significant contributions in shaping a harmonious and tolerant society in Indonesia through their teachings that emphasize values of virtue and cooperation. The order also participates in economic development through various economic activities and utilize digital technology for disseminating their teachings in order to reach a wider audience. This research employed netnography as a qualitative research method and Siberian Media Analysis as a data analysis technique. The study was conducted on the official social media accounts of Tarekat Qadiriyya and Naqsyabandiyya on Instagram and the TQNNews.com website. The research findings indicate that the order has successfully utilized digital technology to expand the reach of their teachings and reach a larger audience. The order has an official website and active social media accounts to disseminate their teachings and promote the activities conducted by the orders. Furthermore, Tarekat Qadiriyya and Naqsyabandiyya has also created a mobile application to facilitate access to information about the orders.